Different Types of Complications in Patients Suffering from B-Thalassemia (Thalassemia Major) - Gul, Riaz; Wazir, Jasim Dil; Rehman, Shandana (Journal of Gandhara Medical and Dental Science, 2017)
INTRODUCTION Thalassemia is a heterogeneous group of gene disorders caused byan inherited mutation or deletion of genes at chromosome 16 & 11 resulting in decreased synthesis of adult hemoglobin. Its incidence is higher in people/children having a positive family history of Thalassemia Among its various types Beta Thalassemia major is the one which requires regular blood transfusions. OBJECTIVES The main objective of the study was to determine the frequency of different types of complications in patients suffering from B-Thalassemia. METHODOLOGY The study was conducted in two private originations in Peshawar i.e. Fatimid Foundation and Hamza Foundation.150 patients) were studied, the study was Cross-Sectional, descriptive type and sampling type was Non-Probability, convenience type sampling. All necessary data were obtained by using semi structured questionnaire, having both closed and open ended questions. Pilot Study was conducted on 15 patients (10%of target questionnaires). After completing the pilot study necessary changes were made in questionnaire and a well-informed, well-designed and organized questionnaire was finalized. An informed consent was taken from respondents and the responses were obtained each from the parents & from children themselves (in case of older children). Data was collected and results were presented in the form of tables and charts. Manual analysis of the data was carried out. RESULTS According to the study, among 150 patients, Splenectomy was done in about 86% patients. Consanguinity among the parents of these patients was about 76%, while awareness only 72% of patients. About 64% patients were having psychological problem. Among neurological problems 57% of patients had headache. Among complications, majority of patients had palpitations about 54% joint pains about 32% & history of bones fractures about 21%. Socioeconomic condition of majority of them was poor about 52%. All of them were taking primary treatment i.e. Blood transfusion &Chelating Therapy to prevent iron overload. CONCLUSSIONS Thalassemia major is a life threatening disease causing morbidity and mortality among those who are not treated properly. The incidence of the disease is high among those with a family history of Thalassemia.